The Emerging Paradigm of Leadership for Future: The Use of Authentic Leadership to Lead Innovation in VUCA Environment - Khan, Muhammad Mumtaz; Ahmed, Syed Saad; Khan, Essa (Frontiers in Psychology, 2021)
This study explicated the mediating role of leader–member exchange (LMX) and identification with the leader linking authentic leadership and innovative work behavior. The data were collected from the three sectors of the service industry. The final sample size obtained was 347. The data were collected both through the Google form and pen-filled questionnaires. SPSS was used to compute demographic profiles and conduct a hierarchal regression, while Smart-PLS was used for evaluating the constructs for their psychometric properties and testing the structural relations as proposed in the model. This study found LMX and identification with the leader to mediate between authentic leadership and the innovative work behavior of the employees.